Improvement of magnetite adsorption performance for Pb (II) by introducing defects - Li, Yuxin; Lv, Guocheng; Liu, Hao; Liu, Xin; Liao, Libing (Frontiers in Chemistry, 2023)
Surface defect engineering is an efficient strategy to enhance the adsorption properties of materials. After calcination in argon, the adsorption capacity of natural magnetite to Pb (II) is significantly improved. The Rietveld refinement, Mössbauer spectrum, and XPS were used to prove the existence of oxygen and cation vacancies in the crystal structure of magnetite after calcination, and it is found that the vacancy content is linearly related to the adsorption amount of Pb (II). This indicates that the increase in the adsorption performance of magnetite after calcination is determined by the vacancy. The adsorption capacity increases from 8 to 26 mg/g when the calcination temperature reaches 700°C. The equilibrium adsorption process of Pb (II) on magnetite can be well fitted to the Langmuir model, and the kinetic adsorption followed a pseudo-second-order mechanism. The improvement of the adsorption performance of magnetite is mainly due to the change in its structure, which depends on the oxidation degree and surface effect of magnetite in the calcination process. This work also provides a theoretical basis for the broad application of magnetite as environmental material.